2006
DOI: 10.1108/17410400610702160
|View full text |Cite
|
Sign up to set email alerts
|

Do women in top management affect firm performance?A panel study of 2,500 Danish firms

Abstract: Do Women in Top Management Affect Firm Performance?A Panel Study of 2500 Danish Firms * Corporate governance literature argues that board diversity is potentially positively related to firm performance. This study examines the relationship in the case of women in top executive jobs and on boards of directors. We use data for the 2500 largest Danish firms observed during the period 1993-2001 and find that the proportion of women in top management jobs tends to have positive effects on firm performance, even aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

72
604
5
35

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 778 publications
(716 citation statements)
references
References 16 publications
72
604
5
35
Order By: Relevance
“…For instance, in Denmark only 7% of the CEOs of companies with more than 50 employees are women [8]. The figure is not very different for Norway [4].…”
Section: World Of Labormentioning
confidence: 81%
See 2 more Smart Citations
“…For instance, in Denmark only 7% of the CEOs of companies with more than 50 employees are women [8]. The figure is not very different for Norway [4].…”
Section: World Of Labormentioning
confidence: 81%
“…These provisions seem to have had an unintended boomerang effect, however. Studies show that children are an important explanatory factor for the divergence in men's and women's careers, even when controlling for level of education [8]. Besides the direct negative effects on experience and human capital of taking long parental leave, there may be more subtle effects on gender norms and stereotyping, especially when women avail themselves of parental leave more frequently than men do.…”
Section: Increasing the Pool Of Potential Female Board Membersmentioning
confidence: 99%
See 1 more Smart Citation
“…In Europe, the evidence of positive associations between gender diversity and financial performance comes from Denmark (Smith et al, 2005) and Spain (Campbell and Minguez-Vera, 2008). In the context of emerging markets, Ararat et al (2010) provide evidence of such positive associations using a sample of the Turkish listed firms.…”
Section: Gender Diversitymentioning
confidence: 97%
“…Smith and Verner (2006) found that the proportion of women in top management jobs had a positive effect on a firm's performance and that the effect depended on the qualifications of female top managers in Denmark. Dawkins et al (2007) argue that both large firms and those which are highly specialized, enjoy higher profit margins, whereas the more capital intensive the firm the lower its profitability.…”
Section: Understanding the Key Conceptsmentioning
confidence: 99%